Volume 6A: Materials and Fabrication 2016
DOI: 10.1115/pvp2016-63578
|View full text |Cite
|
Sign up to set email alerts
|

Unified Viscoplasticity Modeling Features Needed for Simulation of Grade 91 Creep and Fatigue Responses

Abstract: Chaboche unified viscoplasticity model and uncoupled plasticity and creep models (nonunified) are evaluated for their capability in simulating low-cycle fatigue, creep and creep-fatigue responses of Grade 91 steel. The primary objective of this study is to develop a constitutive model incorporating various advanced modeling features for design-by-analysis of elevated temperature power plant components. For validation of the model a broad set of experimental responses of Grade 91 in the temperature range 20–600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chaboche [35] reported that the static recovery term described stress relaxation responses, as well as, other responses influenced by thermally activated mechanisms. Hence, Equation 6is modified by incorporating a static recovery term, the 3rd nonlinear hardening term in Equation (9). The introduction of static recovery term in each back stress allows additional viscosity, which is able to simulate the additional relaxation and creep deformation under low-strain rate [23].…”
Section: Modification Of the Kinematic Hardening Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Chaboche [35] reported that the static recovery term described stress relaxation responses, as well as, other responses influenced by thermally activated mechanisms. Hence, Equation 6is modified by incorporating a static recovery term, the 3rd nonlinear hardening term in Equation (9). The introduction of static recovery term in each back stress allows additional viscosity, which is able to simulate the additional relaxation and creep deformation under low-strain rate [23].…”
Section: Modification Of the Kinematic Hardening Rulementioning
confidence: 99%
“…In USC power plants, creep damage accumulates during steady operation at elevated temperature, whereas start-up and shut-down induce fatigue damage, resulting in fatigue-creep damage interactions [6][7][8]. These complex damage interactions often lead to premature failure of high temperature USC power plant components, which were originally designed for steady creep only [9]. In order to assess remaining fatigue life of existing USC plants with increased number of start-up and shut-down cycles, it is essential to understand the fatigue-creep failure mechanisms and develop robust constitutive models towards developing a simulation-based life estimation and high temperature design methodologies.…”
Section: Introductionmentioning
confidence: 99%